Advances in Food and By-Products Processing Towards a Sustainable Bioeconomy - Kachrimanidou, Vasiliki (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The bioeconomy initially focused on resource substitution, including the production of biomass from various resources; its conversion, fractionation, and processing by means of biotechnology; and chemistry and process engineering towards the production and marketing of food, feed, fuel, and fibre. Nevertheless, although resource substitution is still considered important, the emphasis has been recently shifted to the biotechnological innovation perspective of the bioeconomy, in terms that ensure environmental sustainability. It is estimated that around one-third of the food produced for human consumption is wasted throughout the world, posing not only a sustainability problem related to food security but also a significant environmental problem. Food waste streams, mainly derived from fruits and vegetables, cereals, oilseeds, meat, dairy, and fish processing, have unavoidably attracted the interest of the scientific community as an abundant reservoir of complex carbohydrates, proteins, lipids, and functional compounds, which can be utilized as raw materials for added-value product formulations. This Special Issue focuses on innovative and emerging food and by-products processing methods for the sustainable transition to a bioeconomy era.